Flow test of microfluidic devices - Lee, Jocelyn Yu Qi (2014)
The aim of this report is to study and understand the characteristics of droplets generated using a cross-junction microfluidic device made from Polymethyl-methacrylate (PMMA). Deionised water were dispersed into mineral oil with Span 80 surfactant in square microchannels 200 x 200 μm wide to generate monodispersed W/O emulsions. By varying the flow rate ratio and flow rates of dispersed and continuous phases, different flow patterns and droplet lengths were obtained. The effect of surfactant on two-phase flow performance was studied and proved that without surfactant droplets were unable to form. The droplet formation transition from dripping to jetting was expressed in terms of the capillary number of the continuous phase, which shows the effects of viscous force and inertia forces between the two phases on droplet formation. Moreover, the effects of the continuous phase and dispersed phase viscosity on droplet length are investigated. The continuous phase was replaced with sunflower oil to increase the viscosity of the continuous phase. Different concentrations of glycerol were added to DI water to increase the viscosity of dispersed phase. The coefficient of variation in droplet lengths was then calculated to verify the monodispersity of the droplets formed.